(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: This article has developed a technology for the gross excavation of complex ore bodies with interlayers and rock inclusions, which provides an increase in the completeness and quality of mineral extraction from the subsoil, ensuring safe treatment conditions and eliminating the likelihood of blast hole destruction.